Crisis, Liturgy, and Communal Identity: The Celebration of the Hispano-Mozarabic Rite in Toledo, Spain as a Case Study - Nathan P. Chase (Religions, 2022)
The Hispano-Mozarabic Rite is a helpful case study for liturgists interested in the construction of community identity across time and in light of various types of crises. From the 6th century to today, a number of internal and external crises—political and ecclesial—have shaped the Rite and have threatened its continued existence. From the Arab invasions in 711 CE, the Rite has been key to the preservation of the Mozarab community, the group of Christians who remained in Muslim-ruled Spain and continued to celebrate the Rite. The Rite is key to their self-understanding and preservation. At the same time, the Rite has been coopted throughout its history for burgeoning Spanish nationalist visions. It has also challenged the centralized ecclesiology of the Roman Catholic Church. In order to shed light on the relationship between crisis and communal identity in this tradition, this article will begin with a historical study of the Rite. The second half of this article will look at the modern celebration of the Rite in Toledo through the use of participant observation. This will reveal the way several communities (the Mozarabs and Spaniards) have used the Rite to navigate various crises throughout history.